An initial health economic evaluation of pharmacogenomic testing in patients treated for childhood cancer with anthracyclines. Issue 3 (22nd December 2017) - Dionne, Francois; Aminkeng, Folefac; Bhavsar, Amit P.; Groeneweg, Gabriella; Smith, Anne; Visscher, Henk; Rassekh, Shahrad Rod; Ross, Colin; Carleton, Bruce
Abstract: Background: Anthracyclines are a class of highly effective chemotherapeutic drugs commonly used to treat cancer patients. Anthracyclines, however, are associated with the development of serious adverse reactions, including anthracycline‐induced cardiotoxicity (ACT). It is not possible, within current practice, to accurately individualize treatment to minimize risk. Procedure: Recently, genetic variants have been associated with the risk of ACT in children. Building on these findings and the related genetic test, a predictive model was developed which classifies pediatric patients by their risk of developing ACT. We assessed the value of this ACT‐predictive risk classification in addressing ACT. Results: With current care, the estimated average lifetime cost of ACT is $8, 667 per anthracycline‐treated patient and approximately 7% of patients are expected to die from ACT. The projected impact of the information from the new predictive model is a 17% reduction in the risk of mortality from ACT and savings of about 6%: lives saved and lower costs. Conclusion: The newly identified genetic variants associated with the risk of ACT provide information that allows a more reliable prediction of the risk of ACT for a given patient and can be obtained at a very moderate cost, which is expected to lead to meaningful progress in reducing harm and costs associated with ACT.